Effects of a homeopathic complex on the performance and cortisol levels in Nile tilapia (Oreochromis niloticus) - Merlini, Luiz Sérgio; Vargas, Lauro; Piau Jr., Ranulfo; Ribeiro, Ricardo Pereira; Merlini, Natalie Bertelis (Thieme, 2013)
Background: Intensive fish farming results in stress adversely effecting the performance of farmed fish. Plasma cortisol is a validated measure of stress in fish. We evaluated the effect of a homeopathic complex on the cortisol level of Nile tilapias (Oreochromis niloticus). Method: 60 animals with approximate average weight of 100 g each at the start of experiment were randomly distributed in six glass fiber water tanks, capacity 1000 liters, with a daily water renewal rate of 20%. They received one of two treatments: 30 animals in control treatment and 30 animals receiving the homeopathic complex Homeopatila 100. On days 1, 30 and 60, all fish were anesthetized and blood was collected by puncture on the caudal vein, to determine the levels of circulating cortisol. Results: At the end of the experiment the fish receiving a homeopathic complex, had significantly lower circulating cortisol level (17.96 ng/mL ± 0.95) than the control group (38.68 ng/mL ± 1.21) (p < 0.05). Conclusions: Cortisol levels were significantly lower in the treated group than control, and the fish were larger in the treated group. © 2013 The Faculty of Homeopathy.
Keywords: Cortisol; Homeopathy; Nile Tilapia (Oreochromis niloticus); Stress